A study on the effect of sales revenue and overhead cost towards Malayan Banking Berhad (Maybank) profitability / Nor Aziela Kamaruddin - Kamaruddin, Nor Aziela (Faculty of Business and Management, 2011)
These researches focus on the relationship between profitability with sales revenue and overhead cost of Maybank. The purpose of the research is to know whether the high – profit margin like Maybank should decrease in sales revenue in order to increasing in profitability or vice versa. Moreover, it to determine the overhead cost have influenced in profitability or not. In addition, by doing these researches the researcher will know whether there are any significant relationships between variables. This relationship can be test by analysis descriptive result from E-vies software. These researches been conducted by using secondary data from annual report of Maybank from year 1999 until 2010. The researcher finding show that sales revenue and profitability have negative relationship which is the decreasing in sales revenue will make increasing in profitability. On other hand, the overhead cost shows positive relationships with profitability prove that the increasing in overhead cost will make profitability also increasing.